Porous silicon prepared by photo electrochemical etching assisted by laser - Falah A-H Mutlak (Iraqi Journal of Physics, 2019)
Porous silicon (PS) layers are prepared by anodization for different etching current densities. The samples are then characterized the nanocrystalline porous silicon layer by X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), Fourier Transform Infrared (FTIR). PS layers were formed on n-type Si wafer. Anodized electrically with a 20, 30, 40, 50 and 60 mA/cm2 current density for fixed 10 min etching times. XRD confirms the formation of porous silicon, the crystal size is reduced toward nanometric scale of the face centered cubic structure, and peak becomes a broader with increasing the current density. The AFM investigation shows the sponge like structure of PS at the lower current density porous begin to form on the crystalline silicon, when the current density increases, pores with maximum diameter are formed as observed all over the surface. FTIR spectroscopy shows a high density of silicon bonds, it is very sensitive to the surrounding ambient air, and it is possible to oxidation spontaneously.